Report of the Independent Monitoring Mechanism regarding the implementation of the UN Declaration on the Rights of Indigenous Peoples in Aotearoa New Zealand, June 2018 - Whare, Tracey; Charters, Claire; Ngatai, Jessica (2018)
Keywords: governance; iwi politics; matike mai

Principles of Māori Data Sovereignty - Te Mana Raraunga (Te Mana Raraunga, 2018)
Keywords: data sovereignty; kaitiakitanga; kotahitanga; manaakitanga; rangatiratanga; tikanga | indigenous law; whakapapa; whanaungatanga

Governance of Māori Data - Hudson, Māui; Silveira, Tumanako (Ngā Pae o te Māramatanga, 2018)
Keywords: data; data sovereignty; indigenous data sovereignty

Report of Matike Mai Aotearoa – The Independent Working Group on Constitutional Transformation (2018)
This report is the result of 252 hui between 2012 and 2015. The Working Group was established at a meeting of the Iwi Chairs’ Forum in 2010 with Terms of Reference: “To develop and implement a model for an inclusive Constitution for Aotearoa based on tikanga and kawa, He Whakaputanga o te Rangatiratanga o Niu
Keywords: constitutional transformation; iwi; matike mai